Gnb5 is a negative regulator of the BACE1-mediated Aβ generation and ameliorates cognitive deficits in a mouse model of Alzheimer's disease. - Shaokun Chen; Jiechao Zhou; Shuzhong Wang; Erqu Chen; Kai Zhuang; Raozhou Lin; Chensi Liang; Dan Can; Huifang Li; Jing Li; Jie Zhang (PLoS Biology)
β-Amyloid (Aβ) is generated from the amyloid precursor protein (APP) through sequential cleavage by β-site APP-cleaving enzyme 1 (BACE1) and γ-secretase, where BACE1 acting as the rate-limiting enzyme. Elevated BACE1 levels in the brains of Alzheimer's disease (AD) patients implicate that dysregulated BACE1 expression is crucial to AD pathogenesis. However, the underlying regulatory mechanisms remain unclear. Here, we identified that the G protein subunit β5 gene (Gnb5), a component of the G protein-coupled receptor (GPCR) signaling pathway, is significantly downregulated in both human AD patients and AD mouse models. Conditional knockout of Gnb5 in excitatory neurons resulted in cognitive impairments, whereas adeno-associated virus (AAV)-mediated overexpression of Gnb5 in the hippocampus ameliorated cognitive deficits and reduced Aβ deposition in 5xFAD mice. Mechanistically, we demonstrated that Gnb5 interacts with BACE1, modulating its expression and potentially influencing Aβ generation. We further identify the first tryptophan-aspartate domain (WD domain) of Gnb5 and the Ser81 residue as crucial for this regulation. Expression of this WD domain alone is sufficient to reduce Aβ deposition in 5xFAD mice, whereas a point mutation at Ser81 (S81L) abolishes this effect. Overall, our findings establish Gnb5 as a negative regulator of the BACE1-APP processing axis and unveil mechanistic insights into its role in Aβ-mediated AD pathogenesis.